Blood pressure response to percutaneous transluminal angioplasty for renovascular hypertension: an overview of published series. - Ramsay, L E (1990)
OBJECTIVE--To evaluate the efficacy and safety of transluminal angioplasty in the treatment of renovascular hypertension. DESIGN--Overview of 10 published case series. SETTING--Mostly tertiary referral centres. PATIENTS--691 Patients treated by angioplasty for renovascular hypertension, 464 for atherosclerotic stenosis, 193 for fibromuscular stenosis, and the remainder mainly for post-transplant stenosis. The inclusion criteria varied considerably between studies. INTERVENTIONS--Percutaneous transluminal renal artery angioplasty (successful or attempted); prophylaxis against restenosis in most cases. Policies on antihypertensive drug treatment and follow up varied. MAIN OUTCOME MEASURES--Blood pressure response as defined in the individual papers, with each patient classified as either cured, improved, or failed. Each study used a different definition of improvement in blood pressure. Complication rates. RESULTS--Follow up data were available for 670 patients. The procedure was technically successful in 611 patients (88%). The overall cure rate for hypertension was 24% (163 patients) and a further 43% (286) were "improved." There were large and significant variations between studies in the rate of technical success and also the blood pressure outcome. In each series patients with fibromuscular lesions, had a higher cure rate than those with atherosclerotic lesions (overall cure 50% v 19% odds ratio 3.9, 95% confidence interval 2.6 to 6.0). Complications were reported in 63 (9%) patients and three patients died (0.4%). CONCLUSIONS--The evidence for the value of angioplasty in treating renovascular hypertension has serious limitations. Angioplasty for fibromuscular disease seems to be worth while, but for atherosclerotic lesions the benefit appears to be small and its efficacy needs to be compared with medical therapy in randomised trials. These findings emphasise the importance of early formal evaluation of new therapeutic techniques.